Effect of Environmental and Social Cost on Performance of Manufacturing Companies in Nigeria - Iheduru, Ngozi. G; Chukwuma, Ike Romanus (International Journal of Accounting & Finance Review, 2019)
This study examines the effect of environmental and social costs on performance of manufacturing companies in Nigeria. The objectives of this study are to examine the relationship between environmental and social costs and performance of manufacturing companies in Nigeria. The data for the study were collected from annual reports and accounts of fourteen (14) randomly selected manufacturing companies in Nigeria. The data were analyzed using multiple regression models. The key findings of the study shows that there is significant negative relationship between Environmental and social costs and Return on Capital Employed (ROCE) and Earnings per share (EPS) and a significant positive relationship between environmental and social costs and Net Profit Margin (NPM) and Dividend per Share (DPS). Based on this it was recommended that government should give tax credit to organizations that comply with its environmental laws in order to reduce their environmental costs and that environmental reporting should be made compulsory in Nigeria so as to improve the performance of organizations and the nation as a whole.